G295(P) Antimicrobial prescribing patterns in fever related admissions to a tertiary hospital paediatric emergency department in china. (May 2019) - Mao, S; Song, P; Zhang, JS; Deng, JK
Abstract : Background: Children have high rates of antimicrobial contributing to worldwide antimicrobial resistance. Studies show that antibiotic prescribing rates are high in China. Antibiotic consumption in paediatric emergency medicine is high and results in poorly targeted antibiotic use. The clinicians' antibiotic prescribing rationale must be monitored and refined in order to ensure smarter antibiotic prescribing in paediatric emergency medicine. Aim: In this study, we aim to explore the antimicrobial prescription patterns in the management of acute febrile presentations in a large Chinese children's hospital emergency department (ED). Methods: This is a retrospective cohort study using a 24 hour point prevalence survey collecting clinical and antimicrobial prescription data from pediatric patients with fever who visited the ED from 24th of May 2018 0:00am to 25th of May 2018 0:00am. In this study, fever/pyrexia is defined as (in accordance to local fever management guidelines): Temperature (≥37.3°C) Or parental report of fever Results: A total of 604 cases were included in this study. The median age was 2.2 years (range 3 months – 15.2 years). Abnormal white cell counts (44%), neutrophil counts (50%), platelet counts (44%) and CRP (18%) counts were recorded. Further investigations (micro-organism cultures and imaging) were conducted in 3% of cases. 32% of the pyrexia cases were prescribed antibiotics. Of these, 24% were prescribed to patients whom had no recorded investigations. 89% of antibiotic prescriptions were for a single antibiotic. No more than 2 antibiotics were prescribed at one time. The most common clinical indication for antimicrobial use was Upper Respiratory Tract Infections (URTI) (70%). The 3 most frequently prescribed antibiotics were 2nd Generation Cephalosporins (2GC) (52%), 3rd Generation Cephalosporins (3GC) (17%) and 1 st Generation Cephalosporins (1GC) (15%). Conclusion: Antibiotics are commonly prescribed in paediatric emergency medicine and in China. From the data shown above, there may be over-use of antibiotics in URTI management and antibiotics are being prescribed with insufficient clinical context with an overuse of 2GCs in Chinese paediatric EDs. We recognise larger scale studies are needed in the future to further assess our conclusions in multicentre settings at different time periods in the year.